PROTECTION OF HUMAN RIGHTS RELATED TO WORK. GENERAL CHARACTERISTICS OF INTERNATIONAL STANDARDS FOR COMPARISON (World Bulletin of Management and Law, 2024)
In this articleprotection of human labor rightsattention is paid to the general characteristics of the international standards related to training in the case of the Republic of Uzbekistan, and the author emphasizes the expediency of studying the international standards by classifying them into three categories, i.e. United Nations standards on labor and training, Conventions of the International Labor Organization, and Regional normative documents. He also emphasizes that among the international sources, soft rights, which do not have binding legal force for the states, but are considered as a target for the conduct of the country's internal policy, these documents include the recommendations and declarations of the International Labor Organization, the charters of the Council of Europe, and the model legislation of the CIS